A study of inter-stratum propagation of hydraulic fracture of sandstone-shale interbedded shale oil. (November 2022) - Suo, Yu; Su, Xianheng; Wang, Zijian; He, Wenyuan; Fu, Xiaofei; Feng, Fuping; Pan, Zhejun; Xie, Kun; Wang, Guanzhong
Highlights: The in-situ stress profile of sandstone-shale interbedded shale oil is obtained. Propagation of hydraulic fractures in the sandstone-shale interbedded anisotropy model is modeled. Different influence factors on hydraulic fracturing propagation are studied. Abstract: The vertical production layer of a shale oil reservoir in the Songnan Region, China, is mainly sandstone-shale interbed, and the reservoir thickness is uneven. As a result of varying interlayer properties, the hydraulic fracture height is hard to increase, and the propagation pattern of the fracture is unclear. In this paper, features of sandstone-shale lithological combination in the Songnan Region were explored by indoor rock mechanics experiments, which clarified the rock mechanics parameters and characterized the anisotropic features. Combined with the well-logging curves, the dynamic and static elastic moduli, Poisson's ratio, and tectonic coefficient were obtained. An evaluation model for crustal stress in the Songnan Region of China was built based on the hydraulic fracturing data. Additionally, a numerical model for 3D propagation of hydraulic fracture was established based on the finite element method to obtain three forms of fracture propagation and the effects of eight parameters, including fracturing fluid injection rate, interface strength, vertical stress, horizontal stress, elastic modulus, etc., on the height and length of hydraulic fracture were investigated. The results showed that increased viscosity and vertical stress of fracturing fluid could effectively increase fracture propagation height, low interface strength, fracturing fluid injection rate, and maximum and minimum horizontal principal stresses, thus favoring the propagation of hydraulic fractures. This study provides some guidance for the efficient development of sandstone-shale interbedded reservoir fracturing.